The Influence of Leverage, Profitability, and Female Director on Financial Distress in Consumer Cyclical and Non-Cyclical Sector Companies Listed on the Indonesia Stock Exchange: Pengaruh Leverage, Profitabilitas dan Female Director Terhadap Financial Distress Pada Perusahaan Sektor Consumer Cyclical dan Non Cyclical yang Terdaftar di Bursa Efek Indonesia - Noviani (Universitas Negeri Padang, 2023)
This study aims to analyze the influence of leverage, profitability, female directors, and financial distress, as well as to analyze the simultaneous and partial effects of leverage, profitability, and female directors on financial distress in cyclical and non-cyclic consumer sector companies listed on the Indonesia Stock Exchange. (IDX) 2017-2021. The method used in this study is a quantitative method with panel data regression analysis techniques. The population in this study are cyclical and non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The research population consisted of 119 companies with a sample selection technique using purposive sampling and obtained a sample of 595 samples. The results showed that leverage had a significant negative effect on financial distress, profitability and female directors had a significant positive effect on financial distress. The research results are expected to provide information from theoretical and practical aspects to academics, government and investors regarding the effect of leverage, profitability, and female directors on financial distress. For future researchers to replace or add to the independent variables and add periods and research objects from other sectors that can cause financial distress. For companies to be able to report financial statements in accordance with the conditions of the company so as to prevent financial distress.